Mechanical Regulation of Protein Translation in the Cardiovascular System - Simpson, Lisa J.; Reader, John S.; Tzima, Ellie (Frontiers in Cell and Developmental Biology, 2020)
The cardiovascular system can sense and adapt to changes in mechanical stimuli by remodelling the physical properties of the heart and blood vessels in order to maintain homeostasis. Imbalances in mechanical forces and/or impaired sensing are now not only implicated but are, in some cases, considered to be drivers for the development and progression of cardiovascular disease. There is now growing evidence to highlight the role of mechanical forces in the regulation of protein translation pathways. The canonical mechanism of protein synthesis typically involves transcription and translation. Protein translation occurs globally throughout the cell to maintain general function but localised protein synthesis allows for precise spatiotemporal control of protein translation. This Review will cover studies on the role of biomechanical stress -induced translational control in the heart (often in the context of physiological and pathological hypertrophy). We will also discuss the much less studied effects of mechanical forces in regulating protein translation in the vasculature. Understanding how the mechanical environment influences protein translational mechanisms in the cardiovascular system, will help to inform disease pathogenesis and potential areas of therapeutic intervention.